Starch and powdered activated carbon amended alginate-biomass beads for metronidazole and bulk organic matter removal: Synthesis, optimization, reaction kinetics and reusability. Issue 5 (October 2021) - Girijan, Sudeeptha; Kumar, Mathava; Gomber, Shweta
Abstract: In this work, biomass immobilized alginate beads were amended with various ratios of starch (0–20%) and powdered activated carbon (PAC: 0–0.1%), and optimum compositions were shortlisted based on simultaneous removal of metronidazole (MNZ) and organic matter from synthetic wastewater. MNZ removal of greater than 80% was achieved for initial MNZ concentration of 1 ppm in 3d with optimum PAC (0.1%) and starch (5%) ratios. The presence of additional carbon substrate (i.e., dextrose) had improved the MNZ removal efficiency. Subsequently, the experiments were conducted with alginate beads amended with 0.1% PAC (A1-C2), 5% starch (A1-S1) and combination of 0.1% PAC and 5% starch (A1-S1-C2) The MNZ removal by PAC and starch amended beads was found to follow the second-order and first-order kinetics, respectively. Compared to starch amended beads, average MNZ, organic carbon and nitrogen removal efficiencies of PAC amended beads were higher by 12%, 32% and 5%, respectively. Moreover, reusability study had shown better stability of PAC (8 cycles) compared to starch (3 cycles). When starch and PAC were added together, the removal efficiencies were better than starch but lower than PAC except in the case of ammonia removal. Among the shortlisted beads, A1-C2 was found to perform best in MNZ, TOC and ammonia removals. PAC addition improved MNZ removal efficiency and the MNZ removal rate. The involvement of both adsorption and biodegradation were established in MNZ removal in all types of beads by FTIR and LC-MS analysis, respectively. However, simultaneous and rapid removal of MNZ along with organic carbon by adsorption paired with subsequent biodegradation demonstrate the applicability of A1-C2 for the treatment of PPCP laden wastewaters. Graphical Abstract: ga1 Highlights: Alginate immobilized biomass beads with starch and powdered activated carbon (PAC) amendments were prepared and characterized. Immobilized beads were applied for metronidazole (MNZ), organic matter and ammonia removal. Biomass amended with PAC was found most beneficial for MNZ, TOC and ammonia removals. Starch helped to improve biotic removal and nitrification. PAC immobilized beads presented a feasible treatment option for PPCP loaded wastewater.